'It's not ideal': Reconsidering 'anger' and 'apathy' in the Brexit vote among an invisible working class. (June 2017) - Mckenzie, Lisa
Media commentary has characterized the working class 'leave' voters in the UK's EU referendum in terms of anger, apathy and frustration. There have been very few genuine attempts to document and interpret the meaning of the 'leave' vote among underprivileged voters who seemed to have voted for an outcome that harms their own interests. This article explores accounts and narratives from working class 'leave' voters through an ethnographic study of the political and social viewpoints of working class communities of East London and of ex-mining towns of Nottinghamshire. The article puts into fuller context the anger and apathy of being 'left out', arguing that being 'left out' has been part of working class political narratives for over 30 years. Going beyond frustration and apathy, a significant part of the narrative of working people was of 'not existing', suggesting certain important linkages with ongoing debates about new ways of conceptualizing class differences and class structures. The article shows how macro-stage political events such as a referendum about Europe can often be usefully illuminated by taking seriously the micro experiences on the ground.